Menjelajahi Adopsi dan Dampak Sistem Pembayaran Digital pada Usaha Kecil Menengah di Pedesaan Pakistan - Raza, Danish (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This research examines the uptake and the role of digital payment systems in rural small and medium enterprises (SME) in Pakistan, an area that has been largely ignored in the literature on the subject due to its urban and developed economy focus. The study explored the drivers, perceived benefits, and barriers to adoption using a qualitative approach stemming out of a comprehensive review of scholarly and policy research and industry insights. Results indicate that when introduced well, mobile wallets, QR payments, and banking apps have the potential to increase the efficiency of operations, lower transaction costs, and increase the number of people who have access to formal finance. The adoption is, however, at a low rate because of poor infrastructure, low digital and financial literacy, tax issues, and security-related fears. The work adds new knowledge by concentrating on rural SMEs and offering context-specific solutions, such as the targeted fintech solutions, infrastructure development, and the campaigns to raise literacy rates, as a way to close the digital divide. These results are practical recommendations to policymakers, financial service providers, and rural businesses to build inclusive digital financial ecosystems.